Clear skies ahead [navigation systems]. - Bretz, E.A (IEEE spectrum)
Several projects aimed squarely at upgrading airplane travel, either by enhancing navigation or by improving communications between pilots and air traffic controllers, drew closer to full implementation in 2001. In mid-June, the US Federal Aviation Administration (FAA), Washington, DC, outlined its 10-year operational evolution plan to improve air travel by rolling out new technology to air traffic control facilities. All the systemwide projects target congestion in the skies and on the runways. For too long a time, too many airports were scheduling too many takeoffs or landings for any given period, driving the numbers of delays up. After 11 September, safer air travel became the burning issue. But congestion will no doubt return to prominence once airlines resume full schedules. Meantime, the global positioning system (GPS) satellite constellation and improved situational awareness tools are beginning to enhance safety now, and will alleviate congestion when it returns